FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR MAHASISWA PROGRAM BEASISWA PEGUNUNGAN BINTANG DI UNIVERSITAS KRISTEN SATYA WACANA SALATIGA DAN UPAYA UNTUK MENINGKATKANNYA - Lewi Lepki; Nani Mediatati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the internal and external factors influencing the learning motivation of Pegunungan Bintang scholarship recipients at Satya Wacana Christian University (UKSW), Salatiga, and identifies efforts to improve it. Utilizing a descriptive qualitative approach, this research involved 100 purposely selected students, consisting of 50 students with high GPAs and 50 students with low GPAs. Data were collected through structured interviews, direct observation, and documentation, and then validated through source and technique triangulation. The results indicate that students with low GPAs are primarily constrained by limited academic abilities, weak independent study habits, and difficulties in cultural adaptation. Conversely, students with high GPAs are supported by stronger academic abilities, a high willingness to learn, family support, and financial scholarship assistance. Pre-university mentoring and government matriculation programs, along with academic counseling, guidance, and adaptation workshops from UKSW, contribute positively to student adjustment. This study concludes that coordinated support from the local government, university, and family is crucial to strengthening learning motivation, overcoming adaptation barriers, and improving academic achievement among scholarship recipients.